Wildlife policy, the food system and One Health: a complex systems analysis of unintended consequences for the prevention of emerging zoonoses in China, the Democratic Republic of the Congo and the Philippines - Zhuoyu Wang; Tarra L Penney; Mala Ali Mapatano; Chloe Clifford Astbury; Janielle Clarke; Kathleen Chelsea Togño; Shital Desai; Anastassia Demeshko; Russel Aguilar; Angran Li; Zhilei Shi; Cary Wu; et al. (BMJ Global Health)
Introduction Evolving human–wildlife interactions have contributed to emerging zoonoses outbreaks, and pandemic prevention policy for wildlife management and conservation requires enhanced consideration from this perspective. However, the risk of unintended consequences is high. In this study, we aimed to assess how unrecognised complexity and system adaptation can lead to policy failure, and how these dynamics may impact zoonotic spillover risk and food system outcomes.Methodology This study focused on three countries: China, the Democratic Republic of the Congo (DRC) and the Philippines. We combined evidence from a rapid literature review with key informant interviews to develop causal loop diagrams (CLDs), a form of systems map representing causal theory about system factors and interconnections. We analysed these CLDs using the ‘fixes that fail’ (FTF) systems archetype, a conceptual tool used to understand and communicate how system adaptation can lead to policy failure. In each country, we situated the FTF in the wider system of disease ecology and food system factors to highlight how zoonotic risk and food system outcomes may be impacted.Results We interviewed 104 participants and reviewed 303 documents. In each country, we identified a case of a policy with the potential to become an FTF: wildlife farming in China, the establishment of a new national park in the DRC, and international conservation agenda-setting in the Philippines. In each country, we highlighted context-specific impacts of the FTF on zoonotic spillover risk and key food system outcomes.Conclusion Our use of systems thinking highlights how system adaptation may undermine prevention policy aims, with a range of unintended consequences for food systems and human, animal and environmental health. A broader application of systems-informed policy design and evaluation could help identify instruments approporiate for the disruption of system traps and improve policy success. A One Health approach may also increase success by supporting collaboration, communication and trust among actors to imporove collective policy action.